Advances in application of CRISPR-Cas13a system - Zhang, Yue; Li, Shengjun; Li, Rongrong; Qiu, Xu; Fan, Tianyu; Wang, Bin; Zhang, Bei; Zhang, Li (Frontiers in Cellular and Infection Microbiology, 2024)
Abstract Clustered Regularly Interspaced Short Palindromic Repeats (CRISPRs) and CRISPR-associated (Cas) proteins serve as an adaptive immune system that safeguards prokaryotes and some of the viruses that infect prokaryotes from foreign nucleic acids (such as viruses and plasmids). The genomes of the majority of archaea and about half of all bacteria contain various CRISPR-Cas systems. CRISPR-Cas systems depend on CRISPR RNAs (crRNAs). They act as a navigation system to specifically cut and destroy foreign nucleic acids by recognizing invading foreign nucleic acids and binding Cas proteins. In this review, we provide a brief overview of the evolution and classification of the CRISPR-Cas system, focusing on the functions and applications of the CRISPR-Cas13a system. We describe the CRISPR-Cas13a system and discuss its RNA-directed ribonuclease function. Meanwhile, we briefly introduce the mechanism of action of the CRISPR-Cas13a system and summarize the applications of the CRISPR-Cas13a system in pathogen detection, eukaryotes, agriculture, biosensors, and human gene therapy. We are right understanding of CRISPR-Cas13a has been broadened, and the CRISPR-Cas13a system will be useful for developing new RNA targeting tools. Therefore, understanding the basic details of the structure, function, and biological characterization of CRISPR-Cas13a effector proteins is critical for optimizing RNA targeting tools. Keywords CRISPR-Cas system; CRISPR-Cas13a; Genome editing; Molecular diagnosis; Gene therapy